Why are oral shift reports kept in health care institutions when health care professionals have access to electronic health records? A qualitative study. - Deinboll, Anne; Oddvang, Tone (Nordisk Tidsskrift for Helseforskning, 2021)
Background: Oral shift report has a long tradition in the health service. Electronic health record documentation is available, it is argued that written information can replace the oral transmission of patient information. Health institutions have replaced oral shift reports with “silent reporting”. Aim: To develop knowledge about which topics healthcare professionals talked about during shift reports. Method: Qualitative approach, analyzed by Krippendorff’s content analysis. Nursing students sampled data from oral shift reports. Result: Organizational conditions, care and treatment were most discussed. Professional conditions, staff matters, and frustration were often discussed. Private talk occupied a small part of the shift reports. Conclusion: The shift reports contain more than an exchange of patient information and must receive greater focus while the development of electronic health records (EHR) is ongoing. Streamlining the health service, without an impact assessment of a reduction of oral shift reports, can lead to a deterioration in the quality of the nursing service and patient safety. The nurses’ organizational activities can be disguised in the term report.